Ediacaran metazoan fossils with siliceous skeletons from the Digermulen Peninsula of Arctic Norway. (May 2021) - Moczydłowska, Małgorzata; Kear, Benjamin P.; Snitting, Daniel; Liu, Lei; Lazor, Peter; Majka, Jarosław
Abstract: In this study, a new assemblage of Ediacaran metazoan fossils is reported from the basal Stáhpogieddi Formation on the Digermulen Peninsula of Arctic Norway, including Anulitubus n. gen. Moczydłowska in Moczydłowska et al., Anulitubus formosus n. gen. n. sp. Moczydłowska in Moczydłowska et al., Coniculus n. gen. Moczydłowska in Moczydłowska et al., Coniculus elegantis n. gen. n. sp. Moczydłowska in Moczydłowska et al., Fistula n. gen. Moczydłowska in Moczydłowska et al., and Fistula crenulata n. gen. n. sp. Moczydłowska in Moczydłowska et al. The specimens are three-dimensionally preserved and include tubular and conical skeletons that are morphologically distinguished by their body-wall constructions, radial symmetry, polarity, segmentation, and annulation. The skeletons are interpreted to be biomineralized by primary silica based on computed micro-tomographic, petrographic, geochemical, and spectroscopic evidence of originally rigid body wall with layers of constant thicknesses, composed of opal, microcrystalline quartz, and an admixture of carbonaceous material, which differ from the host sediment mineralogy and do not show replacement or encrustation. The fossil-bearing interval immediately overlies strata of Gaskiers age and can be bracketed within 580–541 Ma, but it is estimated to be ca. 575 Ma on the basis of averaged sedimentation rates and biostratigraphic correlations with Ediacaran biota found in up-section deposits of ca. 558–555 Ma. Future new findings of such fossils in different preservation modes and further multi-collector inductively coupled plasma mass spectrometry, which shows the silicon fractionation and traces its biogenic origin versus inorganic mineralization, may corroborate the interpretation of biogenic silicification of these earliest skeletal fossils. UUID: https://zoobank.org/6bccada1-870e-47b0-b819-82685152ea54